Data of thymol dietary supplementation in quail (Coturnix japonica ): linking bioavailability, effects on egg yolk total fatty acids and performance traits - Fernández, María Emilia (2022)
A bi-factorial design combining the effects of the diet supplied (five levels) and time of sampling (five levels) was established for the variables studied: - Five experimental diets (two controls: the basal diet and the basal diet with vehicle solution; and three thymol doses: 2, 4 and 6.25g/kg of feed). - Five times of sampling (one initial sample point; three sample points along the supplementation period and one at the end of the post-supplementation period).